THE IMPROVEMENT OF SHORT STORY WRITING COMPETENCE THROUGH READING NEWS AT THE VI SEMESTER STUDENTS OF THE FACULTY OF TEACHER TRAINEE AND EDUCATION UNMAS DENPASAR - Sri Widiastuti, Ida Ayu Made (JOURNAL OF LANGUAGE AND TRANSLATION STUDIES, 2015)
This classroom action research was conducted due to the facts that the learning activity of short story writing was not an easy thing for the students of Indonesian study program FKIP Unmas Denpasar. An alternative taken was by giving news text to be read by the students prior to writing short stories. The objective of this study were intended to(1) to know the extent of the students’short story writing competence can be improve through reading news, (2) to know the effect of reading news towards the students’ behaviour in short story learning process. This classroom action research was conducted in two cycle using interpretative- descriptive method. The qualitative and quantitative data were then intepretated descriptively. The data collection was carried out by means of administering tes, observation, interview, and questionnaire. The result of pra-tes which was carried out before the learning action was 68.52. The score of short story writing increased after the learning process was conducted. in the first cycle was 82.94 and in cycle II was 86.76. The short story learning processes which were   started by reading news gave significant effect on the behavior changes of the students in writing short story. Consequently, the learning process can produce good and publishable short stories. Penelitian tindakan kelas ini dilatarbelakangi oleh kenyataan bahwa pembelajaran menulis cerita pendek bukanlah hal yang mudah bagi mahasiswa Program Studi Pendidikan Bahasa Indonesia FKIP Unmas Denpasar. Alternatif yang diambil yaitu dengan memberikan teks berita yang akan dibaca oleh mahasiswa sebelum menulis cerpen. Tujuan dari penelitian ini adalah untuk (1) mengetahui berapa besar membaca berita dapat meningkatkan kompetensi menulis cerpen pada mahasiswa;(2) mengetahui pengaruh membaca berita terhadap perubahan tingkah laku mahasiswa dalam proses pembelajaran menulis cerpen. Penelitian tindakan kelas ini dilaksanakan dalam dua siklus dengan  menggunakan metode deskriptif-intepretatif. data-data kuantitatif dan kualitatif dideskripsikan selanjutnya diintepretasikan secara descriptif. Pengumpulan data dilakukan melalui tes, observasi, wawancara, dan angket. Hasil pra-tes yang dilakukan sebelum tindakan adalah 68,52. Nilai menulis cerpen mengalami peningkatan setelah dilakukan pembelajaran. Pada siklus I adalah 82,94, dan pada siklus II adalah 86,76. Pembelajaran menulis cerpen yang didahului dengan membaca berita memberikan pengaruh yang sangat besar terhadap perubahan tingkah laku mahasiswa dalam menulis cerpen. Pembelajaran yang dilakukan menghasilkan cerpen yang baik dan layak untuk diterbitkan.